2016
DOI: 10.1111/joim.12495
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's disease with cerebrovascular disease: current status in the Asia–Pacific region

Abstract: AD+CVD is likely to be under-recognised in Asia. Further research is needed to establish the true prevalence of this treatable and potentially preventable disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(75 citation statements)
references
References 81 publications
2
73
0
Order By: Relevance
“…In Asia, AD + CVD accounts for up to 20% of all dementia cases, and there is some evidence for a higher prevalence of AD + CVD in the Asian region compared with Western populations . Globally, but also in Asia, AD + CVD is thought to be underdiagnosed, primarily due to lack of awareness resulting from a lack of defined diagnostic criteria, but also due to the high cost of investigations, a lack of adequate diagnostic facilities, and other resource constraints . It has been suggested that some Asian epidemiology studies may be influenced by “survivor bias” due to a high proportion of early deaths .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Asia, AD + CVD accounts for up to 20% of all dementia cases, and there is some evidence for a higher prevalence of AD + CVD in the Asian region compared with Western populations . Globally, but also in Asia, AD + CVD is thought to be underdiagnosed, primarily due to lack of awareness resulting from a lack of defined diagnostic criteria, but also due to the high cost of investigations, a lack of adequate diagnostic facilities, and other resource constraints . It has been suggested that some Asian epidemiology studies may be influenced by “survivor bias” due to a high proportion of early deaths .…”
Section: Introductionmentioning
confidence: 99%
“…Clinically overt dementia has a spectrum ranging from mild to severe . Diagnosis involves clinical assessment, neuropsychological evaluation, and often neuroimaging . Core clinical criteria for all‐cause dementia, based on DSM‐5 criteria for neurocognitive disorders, include cognitive impairments and behavioral symptoms that interfere with functioning and activities of daily living (ADL).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of dementia in Asian countries varies from 2% to 13%, with the greatest risk factors being age, female sex, and low education . The high epidemiological variation in Asian countries may be attributable to the different diagnostic criteria used.…”
Section: Trends Of Cognitive Impairment and Dementia In Asiamentioning
confidence: 99%
“…The high epidemiological variation in Asian countries may be attributable to the different diagnostic criteria used. Also, differences in the level of education of respondents can also influence the results, accounting for as much as a twofold difference . Moreover, the number of dementia and cerebrovascular disease in Asia is higher than the number in Western countries …”
Section: Trends Of Cognitive Impairment and Dementia In Asiamentioning
confidence: 99%